A nutritional supplement containing lactoferrin stimulates the immune system, extends lifespan, and reduces amyloid β peptide toxicity in Caenorhabditis elegans. Issue 2 (28th July 2016) - Martorell, Patricia; Llopis, Silvia; Gonzalez, Nuria; Ramón, Daniel; Serrano, Gabriel; Torrens, Ana; Serrano, Juan M.; Navarro, Maria; Genovés, Salvador
Abstract: Lactoferrin is a highly multifunctional glycoprotein involved in many physiological functions, including regulation of iron absorption and immune responses. Moreover, there is increasing evidence for neuroprotective effects of lactoferrin. We used Caenorhabditis elegans as a model to test the protective effects, both on phenotype and transcriptome, of a nutraceutical product based on lactoferrin liposomes. In a dose‐dependent manner, the lactoferrin‐based product protected against acute oxidative stress and extended lifespan of C. elegans N2. Furthermore, Paralysis of the transgenic C. elegans strain CL4176, caused by A β 1‐42 aggregates, was clearly ameliorated by treatment. Transcriptome analysis in treated nematodes indicated immune system stimulation, together with enhancement of processes involved in the oxidative stress response. The lactoferrin‐based product also improved the protein homeostasis processes, cellular adhesion processes, and neurogenesis in the nematode. In summary, the tested product exerts protection against aging and neurodegeneration, modulating processes involved in oxidative stress response, protein homeostasis, synaptic function, and xenobiotic metabolism. This lactoferrin‐based product is also able to stimulate the immune system, as well as improving reproductive status and energy metabolism. These findings suggest that oral supplementation with this lactoferrin‐based product could improve the immune system and antioxidant capacity. Further studies to understand the molecular mechanisms related with neuronal function would be of interest. Abstract : We determiend that a lactoferrin‐based product protected against acute oxidative stress and extended lifespan of Caenorhabditis elegans . Paralysis of the transgenic C. elegans strain CL4176, caused by A β 1‐42 aggregates, was clearly ameliorated by treatment. Transcriptome analysis in treated nematodes indicated immune system stimulation, together with enhancement of processes involved in the oxidative stress response, protein homeostasis processes, cellular adhesion processes, and neurogenesis in the nematode.